Developing windowns-based applications with Microsoft visual basic. Net and microsoft visual C#. Net - Matthew A. Stoecker (Microsoft Press, 2003)
Get self-paced, from-the-source exam preparation and self-assessment for the skills measured by MCP Exams 70-306 and 70-316—core requirements for MCAD and MCSD certification. Features an enhanced testing tool, plus deeper coverage of Microsoft ADO.NET.